Proteome mining of human follicular fluid reveals a crucial role of complement cascade and key biological pathways in women undergoing in vitro fertilization - Jarkovská, Karla; Tylečková, Jiřina; Lišková, Lucie; Halada, Petr; Moos, Jiří; Řežábek, Karel; Gadher, Suresh Jivan; Kovářová, Hana (Journal of proteome research, 2010)
In vitro fertilization (IVF) is fraught with problems and currently proteomics approaches are being tried out to examine the microenvironment of the follicle in order to assess biological and immunological parameters that may affect its development. Additionally, better understanding of reproductive process may help increase IVF birth rate per embryo transfer and at the same time avoid spontaneous miscarriages or life threatening conditions such as ovarian hyperstimulation syndrome. The primary aim of this study was to search for specific differences in protein composition of human follicular fluid (HFF) and plasma in order to identify proteins that accumulate or are absent in HFF. Depletion of abundant proteins combined with multidimensional protein fractionation allowed the study of middle- and lower-abundance proteins. Paired comparison study examining HFF with plasma/serum from women undergoing successful IVF revealed important differences in the protein composition which may improve our knowledge of the follicular microenvironment and its biological role. This study showed involvement of innate immune function of complement cascade in HFF. Complement inhibition and the presence of C-terminal fragment of perlecan suggested possible links to angiogenesis which is a vital process in folliculogenesis and placental development. Differences in proteins associated with blood coagulation were also found in the follicular milieu. Several specific proteins were observed, many of which have not yet been associated with follicle/oocyte maturation. These proteins together with their regulatory pathways may play a vital role in the reproductive process.
Keywords: shluková analýza; Female; Complement C3; fertilizace in vitro; Cluster Analysis; heparansulfát proteoglykany; reprodukovatelnost výsledků; Clusterin; Chromatography, High Pressure Liquid; Signal Transduction; Fertilization in Vitro; Follicular Fluid; Humans; vysokoúčinná kapalinová chromatografie; Proteome; Electrophoresis, Gel, Two-Dimensional; lidé; imunoblotting; Heparan Sulfate Proteoglycans; klusterin; hemolýza; proteom; Reproducibility of Results; ženské pohlaví; komplement C3; signální transdukce; 2D gelová elektroforéza; komplement 4; Hemolysis; folikulární tekutina; Complement C4; Immunoblotting